Extended producer responsibility in India: Evidence from Recykal, Hyderabad - Utsav Bhadra; Prajna Paramita Mishra (Journal of Urban Management, 2021)
In the past few decades in the developed world and more recently in India, Extended Producer Responsibility (EPR) has been viewed as a promising alternative to traditional waste management policy. In most cases it is impractical and infeasible for firms to manage their own EPR operations due to which they outsource it to third parties known as Producer Responsibility Organization (PRO). The article undertakes a case study of a technology driven cloud based waste management company (Recykal) operating in Hyderabad, India in order to study the operation of a PRO and its contribution to EPR in the Indian context. The study of the products and operations of Recykal reveals that its success in EPR can be attributed to 3 factors namely, market expansion, economies of scale and reduction in uncertainty. Furthermore, the study also concludes that operations of PROs like Recykal help to bring the much-needed clarity, monitoring, efficiency, formalization, coordination, choice and accountability in the waste management sector without hindering employment.
Keywords: 710; Waste management; Extended producer responsibility; Producer responsibility organization; India